Osteosarcopenic obesity: the role of bone, muscle, and fat on health. Issue 3 (17th April 2014) - Ormsbee, Michael J.; Prado, Carla M.; Ilich, Jasminka Z.; Purcell, Sarah; Siervo, Mario; Folsom, Abbey; Panton, Lynn
Abstract : Osteopenia/osteoporosis, sarcopenia, and obesity are commonly observed in the process of aging, and recent evidence suggests a potential interconnection of these syndromes with common pathophysiology. The term osteosarcopenic obesity has been coined to describe the concurrent appearance of obesity in individuals with low bone and muscle mass. Although our understanding of osteosarcopenic obesity's Etiology, prevalence, and consequences is extremely limited, it is reasonable to infer its negative impact in a population that is aging in an obesogenic environment. It is likely that these individuals will present with poorer clinical outcomes caused by the cascade of metabolic abnormalities associated with these changes in body composition. Clinical outcomes include but are not limited to increased risk of fractures, impaired functional status (including activities of daily living), physical disability, insulin resistance, increased risk of infections, increased length of hospital stay, and reduced survival. These health outcomes are likely to be worse when compared to individuals with obesity, sarcopenia, or osteopenia/osteoporosis alone. Interventions that utilize resistance training exercise in conjunction with increased protein intake appear to be promising in their ability to counteract osteosarcopenic obesity.